Klausula demurrage dalam perjanjian jual beli batubara dan akibat hukumnya - Sunarjo Sunarjo; Titus Setya Darmanto (Jurnal Cakrawala Hukum, 2020)
This demurrage problem has an impact on business operators or companies owning coal because it usually has to be burdened by the payment of demurrage fines that could have resulted in increased costs incurred by businesses in transporting coal. In fact, these legal issues arise due to the lack of caution of business actors when agreeing on an agreement. Then only comes legal awareness when an agreed agreement is problematic. This type of research is empirical legal research with interview and observation data collection methods. The conclusion of the research is that the application of the demurrage clause in the coal purchase agreement at PT. Sinar Rejeki Ekonomi starts with an agreement in the agreement regarding the party's burden in the event of demurrage. In the event of a demurrage, the buyer imposes compensation costs to the seller which is deemed to be late based on the total number of days anchored minus the agreed laytime days so that the amount of delay is found. The length of day the laytime is determined by the buyer is calculated based on the total capacity of the mother vessel load and the daily target set by the buyer and the legal consequences of the demurrage clause in the coal purchase agreement at PT. Sinar Rejeki Ekonomi is when a demurrage occurs, the seller is obliged to pay compensation arising from the duration of the demurrage.How to cite item: Sunarjo, S., Darmanto, T. (2020). Klausula demurrage dalam perjanjian jual beli batubara dan akibat hukumnya. Jurnal Cakrawala Hukum, 11(2), 231-239. doi:https://doi.org/10.26905/idjch.v11i2.4408